2018
DOI: 10.1021/acssuschemeng.7b03101
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Phase Epoxidation of Light Olefins over W and Nb Nanocatalysts

Abstract: Epoxides are among the most important essential building blocks with wide downstream applications in the chemical industry. In this context, rational design of cost-effective catalysts is critical to achieve high atom efficiency during epoxidation processes. Therefore, in this perspective, recent research progress on heterogeneous W and Nb nanocatalysts for facile liquid-phase epoxidation will be critically reviewed in terms of catalyst synthesis, surface characterization and structure–function relationship. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 251 publications
1
35
0
Order By: Relevance
“…For this reason, we moved from titanium(IV)-silica catalysts, that are deeply-studied, although less robust and prone to deactivation when in contact with water-containing media [25][26][27][28], towards niobium(V)-silica systems, which showed promising features in terms of activity, selectivity to epoxides and robustness, also in the presence of aqueous H 2 O 2 [29][30][31][32][33][34][35]. Niobium(V)-containing mesoporous silica catalysts in epoxidation reactions, indeed, comply with the main guidelines of Green and Sustainable Chemistry: they do not require hazardous corrosive reactants, avoiding the use of peroxoacids; they circumvent tedious separation and recovery techniques, thanks to their heterogeneous nature, and, by exploiting the oxidizing properties of hydrogen peroxide, only water and dioxygen, in the case of its decomposition, are formed [36][37][38]. Moreover, niobium-silica catalysts displaying a network of mesopores, either ordered or non-ordered, proved to be suitable solid catalysts where the epoxidation of bulky vegetable oil FAMEs can be carried out, thanks to the easy steric accessibility of their mesoporous channels to substrate molecules [39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we moved from titanium(IV)-silica catalysts, that are deeply-studied, although less robust and prone to deactivation when in contact with water-containing media [25][26][27][28], towards niobium(V)-silica systems, which showed promising features in terms of activity, selectivity to epoxides and robustness, also in the presence of aqueous H 2 O 2 [29][30][31][32][33][34][35]. Niobium(V)-containing mesoporous silica catalysts in epoxidation reactions, indeed, comply with the main guidelines of Green and Sustainable Chemistry: they do not require hazardous corrosive reactants, avoiding the use of peroxoacids; they circumvent tedious separation and recovery techniques, thanks to their heterogeneous nature, and, by exploiting the oxidizing properties of hydrogen peroxide, only water and dioxygen, in the case of its decomposition, are formed [36][37][38]. Moreover, niobium-silica catalysts displaying a network of mesopores, either ordered or non-ordered, proved to be suitable solid catalysts where the epoxidation of bulky vegetable oil FAMEs can be carried out, thanks to the easy steric accessibility of their mesoporous channels to substrate molecules [39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…New Mo complexes with different ligands and new supports with different chemical and physical properties were fast developed in the past few years. We recently summarized catalytic epoxidation of various tungsten and niobium heterogeneous catalysts . Mo complexes have similar properties and behaviors as tungsten species, since they are both high‐Z refractory Group 6 transition metals with a closed‐shell electronic structure and d0 configuration .…”
Section: Introductionmentioning
confidence: 99%
“…We recently summarized catalytic epoxidation of various tungsten and niobium heterogeneous catalysts. [28] Mo complexes have similar properties and behaviors as tungsten species, since they are both high-Z refractory Group 6 transition metals with a closed-shell electronic structure and d0 configuration. [29] However, the activity of tungsten complexes was limited due to the lower solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, ions doping has been always employed to inhibit the phase transformation and stabilize the crystal structure of the cathode materials. [19][20][21] For layered Li-rich materials, the ions, e. g. Al 3 + , [22] Mg 2 + , [23] Y 3 + , [24] Cr 3 + , [25] and Zr 4 + , [26] were reported that enabled to improve the electrochemical performance. However, ions doping would give rise to the decrease in capacity of cathode materials, because of the replacement of active ions for stabilizing the crystal structure.…”
Section: Introductionmentioning
confidence: 99%